Disney's Christmas in the Country - Walt Disney 1982-; Disney Storybook Artists; Disney$1 (Bs Global Design Group.s; Walt Disney Pictures (New York : Grolier Book Club, 1982)
When Kenai, a Native American boy living in the Pacific Northwest in prehistoric times, is transformed into a bear, he learns about the lives of creatures other than man.
Keywords: Metamorphosis -- Fiction; Indians of North America -- Northwest, Pacific -- Fiction; Bears -- Fiction; Prehistoric animals -- Fiction; Human-animal relationships -- Fiction; Northwest, Pacific -- Fiction